PENGARUH EPS, PER, ROE, DAN DER TERHADAP RETURN SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Arisa Nurlitasari (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
This study entitled Effect of EPS, PER, ROE, and DEROn Stock Return in The Companies Pharmacy Sector Listed in Indonesian Stock Exchange. The purpose of this study to determine the effect of EPS, PER, ROE, and DERsimultaneously and partiallyto stock return consumer sector manufacturing companies in Indonesian Stock Exchange. The population of this research is all consumption sectors of manufacturing companies listed on the Indonesia Stock Exchange during the period 2011-2014. Based on these criteria the final sample obtained samples of 9 companies. Financial statement data used are the ones with the accounting year ended December 31, 2011-2014. While the return of data used is the stock return 31 December 2011-31 December 2014. Therefore, the data used in the research are secondary data, to determine the accuracy of the model needs to be tested on some of the assumptions underlying the classical regression model. Deviationclassical assumptions used in this study include Normality Test, Test of utocorrelation,Multikolonieritas Test, andTest heteroscedasticity.The results of the analysis of the data showed a positive effect of EPS and PER significant impact on stock returns. The results of the analysis of the data shows the influence of ROE and DER is positif and not significant to the stock return. Keywords: EPS, PER, ROE, DER, dan Stock Return